Intermittent treatment with farnesyltransferase inhibitor and sulforaphane improves cellular homeostasis in Hutchinson-Gilford progeria fibroblasts - Gabriel, Diana (Oncotarget, 2017)
Hutchinson-Gilford progeria syndrome (HGPS) is a rare genetic condition associated with mutations in the LMNA gene. This disease recapitulates some aspects of normal aging, such as hair loss, thin skin, joint stiffness, and atherosclerosis. The latter leads to heart attack or stroke that causes death at an average age of 14.6 years in children with HGPS. The typical LMNA mutation results in the production of a truncated prelamin A protein, progerin, that remains permanently farnesylated and abnormally associated with the nuclear envelope. Farnesyltransferase inhibitors (FTIs) reverse nuclear structure abnormalities that are characteristic of HGPS cells. The first clinical trial using the FTI, Ionafarnib, demonstrated some improvements in HGPS children and, in particular, showed a decrease in arterial stiffness. Recently, we reported that sulforaphane, an antioxidant derived from cruciferous vegetables, efficiently stimulates autophagy and enhances progerin clearance in HGPS fibroblasts. In the present study, we investigated the effect of combined lonafarnib and sulforaphane treartment in HGPS fibroblast cultures. We report that co-administration of both drugs exerts a synergistic and additive positive effect on autophagy activity but was cytotoxic to HGPS cells. In contrast, intermittent treatment with lonafarnib followed by sulforaphane separately and in repeated cycles rescued the HGPS cellular phenotype. We propose that intermittent treatment with FTI and SFN separately might be a promising therapeutic avenue for children with HGPS.